Prevalence and Risk Factors for Gestational Diabetes Mellitus in Tehran - Ahia Garshasbi; Soghrat Faghihzadeh; Mohammad Mehdi Naghizadeh; Mandana Ghavam (Tehran University of Medical Sciences, 2008)
Objective: To evaluate the prevalence of gestational diabetes mellitus (GDM) and its risk factors in Tehran. Materials and Methods: From March 2002 to October 2004, screening for GDM was performed on 1804 women in Tehran. All pregnant women were referred for a 50 g oral glucose challenge test (OGCT) between 24th and 28th week of gestation. All subjects with an abnormal GCT (blood glucose level ≥130 mg/dl) underwent an oral glucose tolerance test (OGTT) within 1 week after the abnormal screening test. The prevalence of GDM was estimated. Results: The glucose challenge test was positive in 38.1% of cases .The prevalence of GDM for the whole cohort was 6.8%. About 78.6%   of our population were at medium or high risk for GDM and, therefore, would have been screened. The rate of GDM was significantly higher in women with a positive family history of diabetes, positive history of GDM, older age, multiparity, pre-pregnancy obesity, greater weight gain during pregnancy, history of infertility, chronic hypertension, history of stillbirth pregnancies and abortion. After logistic regression analysis, GDM diagnosis was significantly correlated with age (P<0.001), pre-pregnancy BMI (P=0.005), family history of diabetes (P<0.001), history of GDM (P=0. 002), chronic hypertension (P<0.001) and glucosuria during current pregnancy (P<0.001). Conclusion: In populations with medium/high risks for GDM (like the Iranian) universal screening is recommended to identify women with diabetes mellitus.